2001
DOI: 10.1016/s0020-7292(00)00382-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical neoplasia in a developing country utilizing cytology, cervicography and the acetic acid test

Abstract: The sensitivity of cytology alone is not great enough for implementing as a screening test in a developing country where screening programs are often inadequate. Screening with a combination of tests, once or a few times per woman's life, is a more acceptable alternative since it allows for less screening events without sacrifying sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
5
15
0
Order By: Relevance
“…[7] Regarding socio-demographic data of the study group, it was found that 44% of them ranged from 20-30 years old with mean age 33.7 years. This result was in agreement with Cronje et al, 2001 [10] who reported in their study about screening for cervical neoplasia in a developing country utilizing cytology, cervicography and the acetic acid test that their study sample had a mean age of 34.4 years. It was also in agreement with Dhaubhadel et al (2008) [14] who reported in their study about early detection of cervical cancer precursors of cervical cancer by visual inspection of cervix with acetic Acid that their study sample had a mean age of 31.1 years.…”
Section: Discussionsupporting
confidence: 92%
“…[7] Regarding socio-demographic data of the study group, it was found that 44% of them ranged from 20-30 years old with mean age 33.7 years. This result was in agreement with Cronje et al, 2001 [10] who reported in their study about screening for cervical neoplasia in a developing country utilizing cytology, cervicography and the acetic acid test that their study sample had a mean age of 34.4 years. It was also in agreement with Dhaubhadel et al (2008) [14] who reported in their study about early detection of cervical cancer precursors of cervical cancer by visual inspection of cervix with acetic Acid that their study sample had a mean age of 31.1 years.…”
Section: Discussionsupporting
confidence: 92%
“…Some earlier studies have reported VIA sensitivity to be stable with age (Cronje et al, 2001;Sankaranarayanan et al, 2004a), but they suffered from verification bias. In a large study in Guanacaste, Costa Rica, the performance of cervicography, a variant of visual inspection with remote assessment of photographic images of the cervix, was noted to decrease substantially with age (Ferreccio et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…The sensitivity and specificity of pap test accuracy ranges from 11 to 99% and 14 to 97% respectively [25][26][27][28].Whereas reports of cytology sensitivity in detecting cervical neoplasia ranged from 50%-98% [28]. It should be borne in mind that the wide range of variation in the performance of pap smear screening regarding sensitivity and specificity as mentioned by the above studies may have some bearing in the outcome from it based on different setup.…”
Section: Discussionmentioning
confidence: 99%